Creating reusable visual components a consistent look and feel throughout your application. - Pieri, George (XML journal :the ultimate enterprise resource.)
Creating Web pages with HTML can be time consuming so it's critical to create generic visual components that can easily be reused. This will give you a consistent look and feel throughout your application. You'll be able to add new functionality at one location and make it available across multiple Web pages, which can save you a lot of time.